Pendampingan Pemahaman Konsep Aljabar Untuk Menyelesaikan Soal Cerita Berbasis Lingkungan Pada Guru-Guru SD - Yuliza, Evi (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2022)
This community service activity aims to introduce the concept of algebra to solve environmental-based story problems so that the learning process becomes structured, directed and interesting. One of the difficulties experienced by elementary school students in learning mathematics is solving story problems. In this community service activity, elementary school teachers are provided with assistance in understanding algebraic concepts to solve environmental-based story problems. This community service activity is very necessary to improve the skills of elementary school teachers. The method applied in this mentoring activity is through lectures and discussions. Community service activities consist of 4 activities, namely providing material, discussing and filling out questionnaires. This community service activity provides an increase in elementary school teachers’ understanding of the concept of algebra to solve environmental-based story problems. Teachers can also invite and teach students closer to the surrounding environment and can support other lessons.